A Directional CSMA/CA Protocol for mmWave Wireless PANs - Gong, Michelle X; Stacey, Robert; Akhmetov, Dmitry; Shiwen Mao (2010 IEEE Wireless Communication and Networking Conference, 2010)
In this paper, we investigate the problem of medium access control in mmWave wireless personal area networks (WPAN), within which directional antennas are used to combat the high path loss incurred in the 60GHz frequency band. The conventional CSMA/CA protocol does not work well with directional antennas due to impaired carrier sensing at the transmitters. We explain why existing directional MAC protocols do not work well at 60GHz and propose a novel directional CSMA/CA protocol designed specifically for 60GHz WPANs. Instead of relying on physical carrier sensing, the proposed protocol adopts virtual carrier sensing and relies on a central coordinator to distribute network allocation vector (NAV) information. Both performance analysis and simulation study show that the proposed mechanism incurs low overhead and has robust performance even when the network is heavily congested.